CULTURAL DIFFERENCES IN ENGLISH AND UZBEK MEDIA ADVERTISING - Jontemirova Yulduz Nu'mon qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
The cultural disparities between English and Uzbek media advertising significantly influence the formulation and execution of advertising strategies, impacting various facets such as language and communication style, cultural values and symbols, aesthetics and visual representation, gender roles and stereotypes, as well as socioeconomic factors. An in-depth analysis of these differences offers valuable insights into the complexities of cross-cultural advertising and underscores the importance of cultural sensitivity and adaptation in crafting effective marketing campaigns for diverse global audiences.